An Analysis On the Phenomena Between Free Voluntary Reading (FVR) And Students’ Writing Ability - Pradana, Satria Adi (English Education: Jurnal Tadris Bahasa Inggris, 2016)
This study investigates the phenomena between free voluntary reading (FVR) of Stephen Krashen and students’ writing ability. This study checked and confirmed whether there is a tendentious relationship between students’ free voluntary reading habit and their ability in writing narrative text. The participants of this research were 18 students of senior high school grade X. They were given a writing test and also interviewed to reveal whether or not they have free voluntary reading habit based on the Stephen Krashen theory of FVR. After scoring the students’ writing test and administering the interview, the researcher used descriptive qualitative method to draw the conclusion. The result revealed that students who have the habit of free voluntary reading on their daily life have a good writing ability. This analysis confirmed the theory of FVR of Stephen Krashen. By having the genuine information of FVR habit owned by the students, this analysis cultivated the previous studies on FVR. It is suggested for the next study to set a true experiment and long period study to implement FVR to confirm either the advantage or the controversy of this theory related in language learning.